BAHASA DAN KECERDASAN ANAK - Ratna Wahyu Pusari (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2011)
Languageis a communication tooltoconveyone'sintent orpurpose. In this paper, language development is veryimportant to supportother developments. Today, children?óÔé¼Ôäós language development haslessserious attention. Because mostpeople assumeifchildren can notspeakis a natural thing. Butcommunicationbetween the childcan bewell maintainedwiththe languageso the child canbuild a relationship, and it is notsurprisingthat the languageis consideredasoneindicatorof successof a child. Childrenthat hasa lot oftalking, sometimesreflected ofan intelligentchild. This intelligenceis anabilitytouse wordseffectively, whether oral or written. In other words, coveredall thewaytocommunicate, wherethoughtsandfeelingsexpressed inthe form ofa symbolorsymbolstoexpressasense, such as usingoral, written, signnumbers, painting, and themimicface.